(untitled) (Biological Sciences - PJSIR, 2022)
Tomato (Lycopersicwn esculentum Mill) variety Roma is a major crop growing in Pakistan. Due to its perishable nature, storage is a problem. Attempts were made to investigate the storage of tomatoes using different techniques during 1989-92. Results showed that the ripening of tomatoes variety Rorna can be controlled for 40 days with percentage of fruit rotting 23.80 - 29.79 depending upon the treatments in coarse moistened saw dust or fine moistened saw dust with or without dipping in 0-4% CaCI2 at ambient pressure for 5 min.